Insights into the Evolutionary Conserved Mitochondrial Contact Site and Cristae Organization System in Trypaonsoma brucei Through RNA Interference - Cadena, Lawrence Rudy (Jihočeská univerzita, 2018)
This work aims to give insight into the evolution of the mitochondria by investigating novel properties of the evolutionary conserved mitochondrial contact site and cristae organization system complex within the Excavata clade using Trypanosoma brucei as our model. This study shows that this complex indeed contains diverse properties that are not present in the typically studied Opisthokonta clade: e.g. mammalian and yeast organisms.
Insights into the Evolutionary Conserved Mitochondrial Contact Site and Cristae Organization System in Trypaonsoma brucei Through RNA Interference
Keywords: Mitochondria; Cristae; Trypanosoma; RNA Interference; Mitochondria; Cristae; Trypanosoma; RNA Interference